A cidade como espaço de acolhida : o pensar teológico no contexto do polo naval na cidade de Rio Grande/RS - Pinto, Raphael Colvara (2014)
The aim of this research is to discuss the urban phenomenon and the recent National Political Mobilization Naval Industry, with its unfolding economic, cultural and religious context of the city of Rio Grande / RS. In this perspective, it is essential to analyze the new economic cycle that is now set up and has established a new paradigm of religious and cultural mobility. This goes beyond the geographic and economic city, taken here as a space of subjectivity and belonging. We chose to do a job bibliographical subsidized by theoretical authors like Bauman (1999, 2001, 2004, 2005, 2007), Lypovetski (1986, 2005, 2007), Augé (2012), Brighenthi (2000, 2004), Libânio (1992, 2000, 2001, 2003), among others, who make important contributions to increase the reflection of the theme addressed here. It has been hypothesized that, despite the complexity posed by urban phenomenon, theology can still be a space for dialogue and accommodation in the city, especially the migrant and foreigner